Telehealth as a tool to strengthen and expand the overweight and obesity care line - Gobbi Marchesi, Doglas; Cristina Brunoro Hoppe , Izabel; Louise Sartorio Altoe Toledo , Michelly; de Jesus Lopes, Gileila; Claudia Nascimento , Lilian; Peixoto Soares Miguel , Gustavo; Paula Ribeiro Ferreira, Ana (Seven Editora, 2023)
The objective of this study is to train the multiprofessional team of primary and secondary care about the management of overweight and obese patients. In addition, to share the knowledge of the multiprofessional team of a bariatric and metabolic surgery program about the management of pre and postoperative patients in all related areas (nutrition, psychology, medicine, social work, nursing, physical education, and physical therapy) within the network of care for obese individuals. DOI: 10.56238/pacfdnsv1-033